Experimental investigation of ventilation efficiency in a dentistry surgical room - Oladokun, Majeed; Ali, Maisarah; Osman, Samsul Bahrin; Samsuddin, Niza; Hamzah, Hairul Aini (EDP Sciences, 2016)
As a response to the need to provide an acceptable thermal comfort and air quality in indoor environments, various ventilation performance indicators were developed over the years. These metrics are mainly geared towards air distribution, heat and pollutant removals. Evidence exists of influencing factors on these indicators as centered on ventilation design and operations. Unlike other indoor environments, health care environment requires better performance of ventilation system to prevent an incidence of nosocomial and other hospital acquired illnesses. This study investigates, using in-situ experiments, the ventilation efficiency in a dentistry surgical room. Thermal and hygric parameters were monitored on the air terminal devices and occupied zone over a period of one week covering both occupied and unoccupied hours. The resulting time-series parameters were used to evaluate the room’s ventilation effectiveness. Also, the obtained parameters were benchmarked against ASHRAE 170 (2013) and MS1525 (2014) requirements for ventilation in health care environment and building energy efficiency respectively. The results show that the mean daily operative conditions failed to satisfy the provisions of both standards. Regarding effectiveness, the findings reveal that the surgical room ventilation is ineffective with ventilation efficiency values ranging between 0 and 0.5 indicating air distribution short-circuiting. These results suggest further investigations, through numerical simulation, on the effect of this short-circuiting on thermal comfort, infection risk assessments and possible design improvements, an endeavour that forms our next line of research inquiries.